Perceptions of Quality of Life among Diabetic Patients attending Mosque Road Polyclinic, Kuching - Lim, Pei Ying; Fatin Nabila, Abdul Aziz; Luk, Kuok Jie; Nur Iwana, Abdul Taib (Universiti Malaysia Sarawak, (UNIMAS), 2011)
Diabetes is a chronic disease that affects the patient’s quality of life. This crosssectional study aims to determine the socio-demographic characteristics and health profile of diabetic patients, and the relationship between these factors with quality of life. Data was collected using the Short Form - 36 (SF - 36) questionnaire on diabetic patients at the Mosque Road Polyclinic in Kuching. Data was analyzed using SPSS software. The most significant findings were at the Physical Functioning level of the patients. Those who were < 50 years (p=0.004) and 50-59 years (p=0.010) had better score than ≥70 years; Chinese had higher score than Malays (p=0.001); those who had university level education scored higher than secondary level (p=0.024); private sector workers (p=0.001) and government sector workers (p=0.009) had better score than pensioner; and respondents with co morbid condition scored lower than respondents without co morbid condition (p=0.023). Besides that, respondents with no formal education had significant lower mean score in Vitality (p=0.018) and Emotional Health (p=0.022) than those with university qualification. Respondents with uncontrolled diabetes also had significant lower mean score in Role-Emotional (p=0.004) comparing to respondents with controlled diabetes. Diabetes was proven to give a negative impact on the respondent’s quality of life. Thus, early diagnosis of the disease and aggressive management of glucose level must be emphasized to prevent deterioration of quality of life due to the disease complications.